Investigation on the Effect of Contact Area and Stress Concentration on Slurry Erosion Wear of AA6063 using Hertz contact theory and Numerical Technique - Bhushan D. Nandre; Girish R. Desale (Tribology in Industry, 2023)
The properties of the erodent, namely, size, shape, hardness, density, etc. have dominant effect on mass removal from the target material surface in slurry erosion. The area of contact of the erodent particle mainly depends on its size and shape. This further leads to variation in the stress development at the target surface due to particle impact. Therefore, it is necessary to investigate the effect of area of contact and stress concentration on the target surface due to different particles shapes and sizes. In view of this, in the present investigation AA6063 is selected as target material with three natural erodents, namely, quartz, SiC and alumina. The area of contact of impacting particle with target material surface is calculated by using Hertz contact stress theory and further determined by using ANSYS for similar conditions. The minimum area of contact of 256 µm size alumina particles with AA6063 target material has been observed around 0.82 x 10-4 mm2 and 0.98 x 10-4 mm2 using Hertz contact stress theory and ANSYS, respectively; which produces maximum stress concentration around 99 x 10-3, MPa using both the techniques. The stress concentration results by ANSYS software are compared with Hertz stress results and the maximum percentage error in stress concentration is observed around 4.19 %. The average mass loss per particle from target material surface is observed around 1.35, 1.94 and 2.11 (x 10-12 g) due to impact of quartz, SiC and alumina particles, respectively. The results obtained by Hertz theory and ANSYS software are observed in line with the mass loss per particle determined experimentally. SEM micrographs reveal the material removal mechanism from target material surface.